Exercise attenuates high-fat diet-induced PVAT dysfunction through improved inflammatory response and BMP4-regulated adipose tissue browning - Liu, Xiaojie; Jiang, Xi; Hu, Jing; Ding, Mingxing; Lee, Sang Ki; Korivi, Mallikarjuna; Qian, Yongdong; Li, Ting; Wang, Lifeng; Li, Wei (Frontiers in Nutrition, 2024)
Background Perivascular adipose tissue (PVAT) dysfunction impairs vascular homeostasis. Impaired inflammation and bone morphogenetic protein-4 (BMP4) signaling are involved in thoracic PVAT dysfunction by regulating adipokine secretion and adipocyte phenotype transformation. We investigated whether aerobic exercise training could ameliorate high-fat diet (HFD)-induced PVAT dysfunction via improved inflammatory response and BMP4-mediated signaling pathways. Methods Sprague-Dawley rats (n = 24) were divided into three groups, namely control, high-fat diet (HFD), and HFD plus exercise (HEx). After a 6-week intervention, PVAT functional efficiency and changes in inflammatory biomarkers (circulating concentrations in blood and mRNA expressions in thoracic PVAT) were assessed. Results Chronic HFD feeding caused obesity and dyslipidemia in rats. HFD decreased the relaxation response of PVAT-containing vascular rings and impaired PVAT-regulated vasodilatation. However, exercise training effectively reversed these diet-induced pathological changes to PVAT. This was accompanied by significantly (p < 0.05) restoring the morphological structure and the decreased lipid droplet size in PVAT. Furthermore, HFD-induced impaired inflammatory response (both in circulation and PVAT) was notably ameliorated by exercise training (p < 0.05). Specifically, exercise training substantially reversed HFD-induced WAT-like characteristics to BAT-like characteristics as evidenced by increased UCP1 and decreased FABP4 protein levels in PVAT against HFD. Exercise training promoted transcriptional activation of BMP4 and associated signaling molecules (p38/MAPK, ATF2, PGC1α, and Smad5) that are involved in browning of adipose tissue. In conjunction with gene expressions, exercise training increased BMP4 protein content and activated downstream cascades, represented by upregulated p38/MAPK and PGC1α proteins in PVAT. Conclusion Regular exercise training can reverse HFD-induced obesity, dyslipidemia, and thoracic PVAT dysfunction in rats. The browning of adipose tissue through exercise appears to be modulated through improved inflammatory response and/or BMP4-mediated signaling cascades in obese rats.